Evaluation of the Implementation of Occupational Safety and Health at the Radiology Installation of the Madani Regional Hospital, Pekanbaru City in 2021 - Diniati, Alni; Rahayu, Endang Purnawati; Jepisah, Doni; Herniwanti, Herniwanti; Zaman, M. Kamali (Budapest International Research and Critics University, 2021)
Radiological examination is carried out using a diagnostic imaging tool that emits radiation, therefore radiology installations must pay attention to aspects of the application of workers' occupational safety and health. The purpose of this study was evaluation of the implementation of occupational safety and health at the Radiology Installation of the Madani Regional Hospital, Pekanbaru City in 2021. This study uses qualitative research methods through in-depth interviews, observation and document review. The research informants were 8 people, which were determined based on the snowball sampling technique. The results obtained are standard operating procedures (SOP) for services have been made and have been socialized and implemented by officers but special SOP for occupational health and safety (K3) are not yet available, radiology installation permits are still in process, K3 training has not been implemented, installation facilities and infrastructure radiology is adequate but there are still shortcomings, archive records have been neatly and in detail in accordance with applicable regulations, reports cannot be carried out because the radiology installation is still in the permit process; some management requirements, some radiation protection requirements and technical requirements are not in accordance with applicable regulations, radiology installation safety verification is in accordance with applicable requirements. The conclusion of this study is that the application of K3 Radiology Installation at the Madani Regional Hospital is not in accordance with the regulation of the head of the nuclear energy supervisory agency number 4 of 2020. It is recommended that the Radiology Installation and related parties can complete the licensing file that is still lacking, conduct K3 training, report if the permit has been completed, meet management requirements, radiation protection requirements and technical requirements that are still lacking.